Lanthanide-Doped Upconversion-Linked Immunosorbent Assay for the Sensitive Detection of Carbohydrate Antigen 19-9 - Zhou, Chaohui; Chu, Zhongyun; Hou, Wenyue; Wang, Xiuying (Frontiers in Chemistry, 2021)
Lanthanide-doped upconversion nanoparticles have attracted considerable attention in detection of biological analytes and bioimaging owing to their superior optical properties, including high photochemical stability, sharp emission bandwidth, large anti-Stokes shifts and low toxicity. In this work, we fabricated lanthanide-doped upconversion (UCNPs)-linked immunosorbent assay (ULISA) for the sensitive detection of carbohydrate antigen 19-9 (CA19-9). The design is based on amino functionalized SiO2-coated Gd doped NaYF4:Yb3+, Er3+ upconversion nanoparticles (UCNPs-SiO2-NH2) as a direct background-free luminescent reporter, a secondary anti-IgG antibody (Ab2) were conjugated to the surface of UCNPs-SiO2-NH2 (UCNPs-Ab2), and UCNPs-Ab2 was used for specific targeting of CA19-9. The nanoparticles were well characterized by TEM, SEM, XRD, FI-IR and UV-Vis. The detection process was similar as ELISA. UCNPs was used as signal transducer to replace the color compounds for an enzyme-mediated signal amplification step. An anti-CA19-9 primary antibody (Ab1) was fixed for capturing the CA19-9, and the fluorescence signal was obtained from the specific immunoreaction between UCNPs-Ab2 and CA19-9. Under the optimum conditions, this ULISA shows sensitive detection of CA19-9 with a dynamic range of 5-2000 U/ml. The ULISA system shows higher detection sensitivity and wider detection range compared to traditional ELISA in the detection of CA19-9. This strategy using UCNPs as signal transducer may pave a new avenue for the exploration of rare doped UCNPs in ELISA assay for clinical applications in the future.